ANALYSIS EFFECT OF QUALITY SERVICE AND PATIENT’S KNOWLEDGE OF PATIENTS ATTITUDE OF AWARENESS OF TREATMENT AND ITS IMPACT ON DENTAL PATIENT VISIT AT PUSKESMAS SITU UDIK BOGOR DISTRICT, WEST JAVA, INDONESIA - Lenny Asyita Cahyani; Munaya Fauziah (Universitas Ahmad Dahlan, 2018)
Background: Dental and oral disease attacks almost everyone in the world. Nevertheless, majority of people pay less attention to look after their dental and oral health. Therefore, that case gave rise the severe level. The main cause of severity of dental disease is the disobedience of the patients to the determined medical service standards. Objective: The purpose of this study is to reveal the impact of the service quality and knowledge of the patients with regards to the treatment awareness behavior and to the re-visit of dental patients at community health center (Puskesmas) Situ Udik, Bogor district, west Java, Indonesia 2018. Method: The research design used in this research is quantitative analytics. As for the analysis test, the path analysis is used. The activities were carried out in Dental Polyclinic of Puskesmas Situ Udik in February 2018 where sampling was done by using random sampling system with 143 respondents. Result: The statistic test shows that the factors that influence the patient's re-visit are quality of service (p value = 0.011, contribution 22,5%) and behavior of the patients (p value = 0,045, contribution 17,4%). While the factors that influence the behavior of the patients is quality (p value = 0.000, contribution 45.6%). In addition, simultaneously the quality of services, knowledge as well as behavior affect the re-visit (p value = 0.000 and contribution of 11.6%) Conclusion: 1) to improve the quality of service at Puskesmas Situ Udik and; 2) to provide the patients with education or health promotion in order to improve their knowledge as well as behavior with regards to dental diseases.